(untitled) (Experimental biology, 2015)
On the basis of the analysis of properties of index Hirsch and necessities adequately to estimate quality of scientific publications it is offered to use a citation index - a new indicator citation of scientific articles. On an example of the analysis of citing of publications of employees of faculty of biology and biotechnology many essential lacks of index Hirsch are shown. The offered index of citing of publications in the best degree characterises scientific activity of scientists.